A NOTE ON PRESERVATION OF SPECTRA FOR TWO GIVEN OPERATORS (2018)
We study the relationships between the spectra derived from Fredholm the- ory corresponding to two given bounded linear operators acting on the same space. The main goal of this paper is to obtain sufficient conditions for which the spectra derived from Fredholm theory and other parts of the spectra corresponding to two given operators are preserved. As an application of our results, we give conditions for which the above mentioned spectra corresponding to two multiplication operators acting on the space of functions of bounded p-variation in Wiener’s sense coincide. Additional illustrative results are given too.